2021
DOI: 10.3390/educsci11080414
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Style, Coping Strategies, Stress and Social Support: Associations to the Medical Students’ Perception of Learning during the SARS-CoV-2 Pandemic

Abstract: This study assessed the learning perception of undergraduate medical students on three types of teaching (classical/online/hybrid), in relation to coping strategies, stress, and social support, in the context of the SARS-CoV-2 pandemic. Additionally, we explored gender differences and the perceived usefulness of teaching. 201 students (48 men, 153 women; mean age = 22.900, SD = 2.830) participated in the study. They answered a Multidimensional Scale of Perceived Social Support, a Brief Cope Scale, a Student-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 70 publications
(70 reference statements)
0
19
0
Order By: Relevance
“…Different studies over the last few months have developed the fundamental role played by soft skills in teachers’ and students’ ability to face the situation [ 26 ]. Similarly, different publications have analyzed the levels of stress and burnout in teachers of different educational levels in the pandemic scenario [ 1 , 34 , 35 ], as well as the psychological problems such as depression, anxiety, isolation, and loneliness that the pandemic has caused [ 36 , 37 , 38 ], detecting differences in the levels of stress generated in teachers according to gender [ 39 ], place of residence [ 40 , 41 ], and cultural and social characteristics [ 42 ]. Other studies have analyzed in teachers the relationship between work hours, work–family balance and quality of life (QoL) [ 43 , 44 ], although teachers already reported a low perception of QoL before the COVID-19 pandemic with a significant impact on mental and physical health due to various stress factors associated with work overload [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies over the last few months have developed the fundamental role played by soft skills in teachers’ and students’ ability to face the situation [ 26 ]. Similarly, different publications have analyzed the levels of stress and burnout in teachers of different educational levels in the pandemic scenario [ 1 , 34 , 35 ], as well as the psychological problems such as depression, anxiety, isolation, and loneliness that the pandemic has caused [ 36 , 37 , 38 ], detecting differences in the levels of stress generated in teachers according to gender [ 39 ], place of residence [ 40 , 41 ], and cultural and social characteristics [ 42 ]. Other studies have analyzed in teachers the relationship between work hours, work–family balance and quality of life (QoL) [ 43 , 44 ], although teachers already reported a low perception of QoL before the COVID-19 pandemic with a significant impact on mental and physical health due to various stress factors associated with work overload [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies revealed positive associations between COVID-19-related difficulties and decreased levels of perceived coping with the pandemic. Coping strategies were also influenced by media coverage of the pandemic, and denial and substance use were significantly associated with poor communication, poor time planning, and disrupted studies during the Coronavirus pandemic [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students chose different coping strategies. These negative symptoms were often more pronounced in female students than in male students [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…also reported a 71.26% of the college students in the United States (US) suffering an increase in the level of stress/anxiety during the pandemic with almost half of the participants showed a moderate-to-severe level of depression. Other studies also reported that female students were associated with higher perceived stress (Klaassen et at., 2021) and higher perceived social support (Popa-Velea et al, 2021). Thus, this study aimed to assess the perceived stress level among university students and its relationship to socio-demographic characteristics during the COVID-19 outbreak.…”
Section: Perceived Stress Among University Students During the Covid-...mentioning
confidence: 99%